Development of Interactive Multimedia "ABBD: Aku Bisa Belajar Disiplin" to Improve Student Discipline in Early Childhood Education - Aisyah, Ratu Nur (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study aimed to address low technology utilization and poor student discipline in schools by developing interactive multimedia titled ABBD: Aku Bisa Belajar Disiplin. Using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation), this Research and Development (RnD) study was conducted over six months (March-August 2023) at RA Mutiara Iman. Participants included ten students aged 5–6 years, selected randomly, while media and material experts and field practitioners were purposively chosen for feasibility evaluations. Data were collected through observations, interviews, questionnaires, and documentation. Qualitative data were analyzed using the Miles and Huberman model, while quantitative data were assessed using Likert and Guttman scales. The results showed significant improvement in student discipline, with scores increasing from 66% pre-intervention to 85% post-intervention. Feasibility evaluations by media experts scored 88.9% (very good), while material experts scored 97.7% (very good). Field practitioners, including principals and teachers, rated the multimedia between 95.3%–100% (very good). Trials with students revealed high acceptance, with one-to-one trials scoring 90% and small-group trials scoring 92.5%. The multimedia incorporated audio, video, animations, and interactive buttons, ensuring user-friendly and age-appropriate content. These findings underscore the effectiveness of "ABBD" in improving discipline among early childhood students and highlight the potential for integrating technology into educational practices. The study's limitations include its focus on a small sample size and short-term evaluation, which may restrict the generalizability and understanding of long-term impacts.   Future research should explore its long-term impacts and scalability in diverse educational settings to maximize its broader application.